Homogeneous spin-dephasing time of NV− centre in millimetre-scale 12C-enriched high-pressure high-temperature diamond crystals - Chikara Shinei; Yuta Masuyama; Hiroshi Abe; Masashi Miyakawa; Takashi Taniguchi; Takeshi Ohshima; Tokuyuki Teraji (Communications Materials)
Abstract Negatively charged nitrogen vacancy (NV−) centres in diamond crystals are promising colour centres for high-sensitivity quantum sensors. A long dephasing time (T 2 * > 10 μs) is essential for achieving increased sensitivity and higher uniformity of T 2 * in millimetre-scale diamond is strongly desired for femto-tesla weak magnetic field detection. High uniformity of T 2 * for NV− centres is achieved herein. The median value of T 2 *, <T 2 *>, in the 12C-enriched high-pressure, high-temperature (HPHT) grown diamond with a nitrogen concentration of 1.3 ± 0.4 ppm is 4.5 μs. The variance of T 2 * is only 10% over a millimetre-scale region (1.1 × 1.1 mm2) within the 0.4 mm thick {111} growth sector. <T 2 *> is ~2/3 times the value limited by the dipole-dipole interaction from the electron-spin bath of nitrogen impurities, suggesting that the residual strain gradient in the HPHT diamond crystal partially limits T 2 *. Reducing the strain gradient in diamond crystals provide a pathway to achievement of high sensitivity magnetometry using NV quantum sensing.